Viral Marketing: Mixue the King of Snow Ice Cream—How does this franchise affect the market? - Sungkawati, Endang; Novitasari, Dwi Rizki; Hamad, Salah Ben (CV. Bimbingan Belajar Assyfa, 2023)
The food and beverage (F&B) industry in Indonesia is experiencing rapid growth with an estimated increase of five to seven percent by the end of 2023. One of the main players attracting attention is Mixue, a snow ice cream franchise that has utilized viral marketing strategies to expand its market share. the market. This research aims to analyze the impact of Mixue's viral marketing strategy on consumer interest and purchasing behavior in the Indonesian market. Using a qualitative descriptive approach, this research combines literature analysis from scientific journals published in the last five years. Data was collected through searches on Google Scholar, Vosviewers, Harzing's Publish, or Perish, with the keywords: